The Effect of Public Sector Employment on Women's Labour Market Outcomes - Anghel, Brindusa; de la Rica, Sara; Dolado, Juan J. (Washington, DC: World Bank, 2012)
This paper addresses the role played by Public Sector (PS) employment across different OECD labour markets in explaining: (i) gender differences regarding occupational choices in either PS or private sector, and (ii) subsequent changes in female labour market outcomes. To do so, we provide some empirical evidence about cross-country gender differences in choice of employment in the PS vs. the private sector using the European Community Household Panel (ECHP), in the light of several theories about patterns of gender behaviour in the labour market. We also analyze the main determinants of the hourly wage gaps across these two sectors for males and females separately. Finally, we document the main stylized facts about gender differences in labour market transitions of workers among inactivity, unemployment, working in the PS and working in the private sector.